Childhood adversity and educational attainment: Evidence from Zambia on the role of personality - Rockers, Peter C.; Zuilkowski, Stephanie Simmons; Fink, Günther (Frontiers in Psychology, 2023)
Introduction We examine whether personality traits mediate the association between childhood adversity and educational attainment using longitudinal data from a cohort in Zambia. Methods We fit a structural equation model using data on three forms of childhood adversity—household poverty, stunting as a measure of chronic malnutrition, and death of a parent—and data on the “Big Five” personality traits and educational attainment assessed at 15 years of age. Results We find that childhood poverty and death of a parent are associated with lower openness to experience. Furthermore, openness to experience mediates 93% of the negative association between death of a parent and school enrollment and 19% of the negative association between childhood poverty and enrollment. Discussion Our findings reinforce a diverse and growing body of evidence linking childhood adversity to educational attainment while also placing it in a new light. Future work should continue to examine the biological and psychosocial pathways that determine openness to experience and other personality traits, as well as their role in shaping important life outcomes.